A young child formula supplemented with a synbiotic mixture of scGOS/lcFOS and Bifidobacterium breve M-16V improves the gut microbiota and iron status in healthy toddlers - Chew, Charmaine; Matsuyama, Misa; Davies, Peter S. W.; Hill, Rebecca J.; Morrison, Mark; Martin, Rocio; Codoñer, Francisco M.; Knol, Jan; Roeselers, Guus (Frontiers in Pediatrics, 2024)
Early life gut microbiota development depends on a highly synchronized microbial colonization process in which diet is a key regulator. Microbiota transition towards a more adult-like state in toddlerhood goes hand in hand with the transition from a milk-based diet to a family diet. Microbiota development in the first year of life has been intensively researched; however, studies during toddlerhood remain sparse. Young children's requirement for micronutrients, such as dietary iron, is higher than adults. However, their intake is usually sub-optimal based on regular dietary consumption.The CHaRM trial was a double-blinded, randomized, controlled trial to investigate effects on body composition of a toddler milk compared to unfortified standard cow's milk in healthy children between 1-2 year age in Brisbane (Australia). In this trial a fortified milk with reduced protein content and synbiotics (Bifidobacterium breve M-16V, short-chain galactooligosaccharides and long-chain fructooligosaccharides [ratio 9:1]) and micronutrients added, was compared to a standard unfortified cow's milk. In this study, the effects the intervention on the gut microbiota and its relationship with iron status of toddlers were investigated in a subset of 29 children (18 Active and 11 Control) who completed the CHaRM study.The toddler microbiota consisted mainly of members of the phyla Firmicutes, Bacteroidota and Actinobacteriota.Abundance of Bifidobacterium breve species was quantified and was found to be lower in Control than the Active CHaRM MS group. Analyses of blood iron markers showed an improved iron status in the Active group. We observed a positive correlation between Bifidobacterium abundance and blood iron status. PICRUSt, a predictive functionality algorithm based on 16S ribosomal gene sequencing, was used to correlate potential microbial functions with iron status measurements. This analysis showed that the abundance of predicted genes encoding for enterobactins, a class of siderophores specific to Enterobacteriaceae, is inversely correlated with the relative abundance of members of the genus Bifidobacterium. These findings suggest that healthy children who consumed a young child formula fortified with synbiotics as part of a healthy diet have improved iron availability and absorption in the gut and an increased abundance of Bifidobacterium in their gut microbiome.